Experimental Study on Decomposition and Evaporation Characteristics of N,N,N′,N′-Tetramethylethylenediamine and 1,2,4-Triazole - Jungmin Yu; Seung Wook Baek; Sung June Cho (Energies, 2019)
N,N,N′,N′-Tetramethylethylenediamine (TMEDA) is one of the candidate substances of hydrazine for hypergolic bipropellant applications. In this study, two experimental analyses were performed to investigate the characteristics of TMEDA and TMEDA mixed with 1,2,4-triazole. First of all, thermogravimetric analysis was performed to analyze thermal decomposition process of the candidate materials. During heating, TMEDA started to evaporate at a temperature below its boiling point and 1,2,4-triazole evaporated subsequently. In addition, evaporation behaviors of TMEDA droplets with two concentrations of 1,2,4-triazole (10% and 20% by weight) were studied at various temperatures. A single droplet experimentation was accomplished in a high-pressure chamber using a heating system under atmospheric nitrogen gas condition. Its droplet behavior was recorded with a high-speed camera and the data were post-processed using Visual Basic software to trace the droplet diameter variation. Bubbling and puffing were observed in the case of the TMEDA containing 1,2,4-triazole above 400 °C. As a result, the rate of evaporation was substantially enhanced by increasing the concentration of 1,2,4-triazole at same temperature. However, the evaporation rates after TMEDA evaporation were the same irrespective of the concentration of 1,2,4-triazole.